Personal Income Tax Calculation and Reporting Training - Layon Hocben Hutagaol; Iren Meita; Avincennia Vindy Fitriana; Nelly Nur Fitriani (STMIK Pontianak, 2021)
One of the government's ways, in this case the Director General of Taxes, in optimizing tax revenues is to conduct a tax awareness inclusion program. Tax inclusion to provide an understanding that an important element of the foundation of Republic of Indonesia. Tax inclusion starts from universities, to increase tax awareness of students, teachers, and lecturers. As with the government's intention to optimize taxes and provide tax inclusion, the Bina Insani University campus through Community Service wants to provide training on calculating individual income taxes to students, so that in the future many students who have businesses and become employees can implement tax awareness by providing the best for the country through their income taxes. With this tax training, participants have a better understanding of taxation in general and its functions, calculation of personal income tax and reporting of personal income tax.